CORPUS SOFTARE IN TECHING: EXAMIATION OF LANGUAGE EXPOSURE - Olimboyeva Parizoda (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
In the dynamic field of English as a Foreign Language (EFL) education, corpus-based instruction (CBI) has risen as a transformative approach, enriching language learning and teaching through its diverse applications and a solid theoretical grounding. In linguistic research, corpus linguistics involves the collection and analysis of authentic texts to provide evidence for describing the nature, structure, and use of languages.